PELAKSANAAN PEMBANGUNAN GEDUNG SERBAGUNA PLBN ENTIKONG YANG DILAKSANA OLEH PT NINDYA KARYA (PERSERO) PADA PROYEK PENGEMBANGAN SARANA DAN PRASARANA PENUNJANG PLBN TERPADU KALIMANTAN BARAT - Mahendra, Andi; Rosanti, Indah; Reski, Indah Anjar (RETENSI, 2020)
State Border Crossing Post of Entikong (PLBN) is one of the border points between the state owned by theIndonesian State which is directly adjacent to the State of Malaysia, the state of Sarawak. In the PLBNEntikong area there is a multipurpose building carried out by PT. Nindya Karya (Persero). In this finalproject discusses the systematics and process of implementing the multipurpose building construction inorder to know the management system of a project, volume or backup quantity (Mutual check 100%), RAB,weight, duration of time (Barchart), work methods, and workers' personal protective equipment. In theprocess of reviewing the implementation of the Multipurpose Building construction, the methods used inretrieving data were the methods of observation, interviews, and documentation. In addition, the data wereobtained from the project contracts documents for the development of facilities and infrastructure to supportthe integrated PLBN West Kalimantan. From the review process and stages, the results are obtained,namely: the management system of a project obtained from the project contract document, the volume thathas been crosschecked through the daily monitoring process, the cost budget plan that has been addendumdue to the addition and reduction of volume, the weight of the work after being added the duration of timeafter the workday addendum, making the method of each work item carried out by direct field review, as wellas personal protective equipment used while working.